Food policy research for improving the reform of agricultural input and output markets in Central Asia - Goletti, Francesco; Chabot, Philippe (Elsevier, 2000)
Agriculture is a significant component of the Central Asian economies. Since independence, the republics have implemented agricultural reforms in varying measure, yet production has fallen sharply across the region. The more ambitious agricultural reform programs have included measures aimed at liberalizing agricultural marketing, trade and prices. However, so far the expected supply response has yet to emerge. The objective of this paper is to highlight key policy and research issues surrounding reform of agricultural markets. It summarizes the main features of agricultural performance since the reforms, highlighting trends in grain and cotton, livestock, input use, and trade and analyzes key constraints to improvement of the sector, emphasizing price policy, sequencing problems, and institutional weakness. It presents a research agenda by identifying the main research needs for better agricultural policy design. It calls for more research on input and output market efficiency, private sector development, the effects of reform on farmers, sequencing issues, comparative advantage, water management, land tenure and farm size.